2021
DOI: 10.1007/s12325-021-01731-9
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Versus Preservative-Free Latanoprost for the Treatment of Glaucoma and Ocular Hypertension: A Post Hoc Pooled Analysis

Abstract: Introduction To compare the tolerability and efficacy of a preservative-containing latanoprost (PCL) to a preservative-free formulation of latanoprost (PFL) in patients with open-angle glaucoma or ocular hypertension. Methods A pooled analysis was performed of data from five published studies. The primary outcome was tolerability as evaluated by the severity of hyperemia. The secondary objectives were patient tolerance based on a composite ocular surface disease (OSD) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“… 8 A post hoc pooled analysis of 3 randomized controlled clinical trials and 2 international real-world evidence observational studies including 3610 total patients, which compared patient tolerance and efficacy of preservative-free and preservative-containing latanoprost formulations, found that patients receiving preservative-free latanoprost had reductions in conjunctival hyperemia and ocular surface disease composite score as compared with patients receiving latanoprost with preservatives. 15 Similar reductions from baseline in IOP were found for both formulations. In the open-label RELIEF study of 140 adults with glaucoma or OHT who had stable IOP after ≥3 months of latanoprost with BAK monotherapy and switched to preservative-free latanoprost, IOP-lowering efficacy was maintained over the 90-day study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“… 8 A post hoc pooled analysis of 3 randomized controlled clinical trials and 2 international real-world evidence observational studies including 3610 total patients, which compared patient tolerance and efficacy of preservative-free and preservative-containing latanoprost formulations, found that patients receiving preservative-free latanoprost had reductions in conjunctival hyperemia and ocular surface disease composite score as compared with patients receiving latanoprost with preservatives. 15 Similar reductions from baseline in IOP were found for both formulations. In the open-label RELIEF study of 140 adults with glaucoma or OHT who had stable IOP after ≥3 months of latanoprost with BAK monotherapy and switched to preservative-free latanoprost, IOP-lowering efficacy was maintained over the 90-day study.…”
Section: Discussionsupporting
confidence: 62%
“…The current findings are consistent with other recent publications that collectively support the safety, tolerability, and high rates of patient satisfaction and self-reported quality of life with BAK-free latanoprost formulations, including preservativefree formulations. [8][9][10][11][12][13][14][15] Results of the 12-week primary phase 3 study comparing latanoprost 0.005% without vs with BAK in OAG or OHT, which enrolled 578 patients, demonstrated that substantial reductions from baseline in IOP were maintained for the duration of the study in the latanoprost BAK-free group. 8 TEAEs were mostly mild with comparable incidence between treatment groups, and no significant safety concerns were found for ocular TEAEs (eye pain, ocular and conjunctival hyperemia, VA, eye lid and margin, cornea, anterior chamber, eye pruritus, VF, and iris and eyelash changes) in patients receiving BAK-free latanoprost.…”
Section: Discussionmentioning
confidence: 99%
“…This means that TJO-002 was at least non-inferior to BAK latanoprost in terms of the ability to lower IOP. The reduction of mean IOP at 9 a.m. of the last visit compared with baseline was -8.13 mm Hg (33.16%) for TJO-002 and -7.43 mm Hg (31.05%) for BAK latanoprost, which was consistent with the range of the optimal IOP reduction associated with latanoprost 0.005% (approximately 28%-31%) reported previously [22][23][24] . Aspberg et al [22] reported that latanoprost was associated with a 28% decrease from the baseline IOP.…”
Section: Discussionsupporting
confidence: 86%
“…Aihara et al [26] reported that fewer ocular surface complications without significant IOP changes were observed with BAK-free travoprost than with BAK latanoprost, with a reduced prevalence of superficial punctate keratitis and less hyperemia, in a long-term 12-month prospective study. Harasymowycz et al [23] reported that PF latanoprost showed the same efficacy, along with improved local tolerance, compared with BAK latanoprost. Considering the importance of adherence and the fact that glaucoma requires long-term treatment, local ocular tolerability as well as efficacy is an important factor in preserving the quality of life in patients with glaucoma.…”
Section: Discussionmentioning
confidence: 98%
“…5,12 A post-hoc analysis demonstrated a significant reduction in the ocular surface disease composite score (P,0.001) for patients receiving preservative-free latanoprost versus patients receiving preservative-containing latanoprost with no significant difference in change in IOP (P¼0.312). 13 Reducing exposure to BAK is important for maintaining the integrity of the ocular surface and tear film of patients who may require long-term topical therapy. Limitations of the current study include the 72-hr washout period for patients previously taking other prostaglandin analogs for the reduction of IOP.…”
Section: Discussionmentioning
confidence: 99%